Routing scheme for key-relaying-based quantum key distribution network in wide-area - Chao YANG; Hong-qi ZHANG; Jin-hai SU; Hua-cheng CHEN (网络与信息安全学报)
The existing routing schemes for key relaying QKD network had a limited scope of application and could not satisfy the requirements of the routing issue of wide-area QKD network.A multi-domain routing scheme based on visual link was proposed for QKD network after the analyzing of the characteristics of QKD network and the proposing of the design requirements of routing issue.In this routing scheme,the QKD network was divided into multiple routing areas to reduce the complexity of intra-domain routing,and a visual QKD link striding over the whole key routing area was built to shorten the routing path.Therefore,the routing efficiency can be increased by this scheme.After theoretical analysis,the proposed routing scheme has advantages of fast convergence of routing update,little time delay and low key material cost.